(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
The history of bureaucratic organisation in India commenced when the East India Company made the decision to assume the role of Diwan and take control of the governance of the three provinces that were ceded to them. The Indian situation did not suit the Weberian model of bureaucracy for the majority of British rule. In the provinces, democracy was not established until 1935. Ministerial control over civil servants existed. However, the existence of imperialism made this control more formal than real. The legacy of Indian Administrative Service is based on the model of the Indian Civil Service created by British in India. India has long been concerned about reforming public administration. India is participating in this comprehensive discussion about the reform. The approach of the bureaucracy needs to shift from "only government can do" to "government in partnership with the people can do."